EVALUATION OF COMMERCIALLY AVAILABLE MOZZARELLA CHEESE FOR ITS MELT AND STRETCHING BEHAVIOUR THROUGH FARINOGRAPH-E - S. Inayat; M. Ayaz; T. N. Pasha; M. Abdullah; A. Waheed (Journal of Animal and Plant Sciences, 2014)
Rheology of the solid and melted cheese depends upon their functional properties. Farinograph is used for quality determination of wheat flour dough. Determination of the rheological properties of dough and dough like food materials from Farinograph is easy while study of cheese characteristics is very difficult and complicated. The present study is therefore designed for the possibility of qualitative profile development for studying cheese by using Farinograph. Torque (resistance against farinograph paddles) was measured along with other qualitative parameters (texture, fat globules, protein matrix) and graphs were plotted between torque and time to see changes in torques at different temperatures (20, 30, 40, 50 and 60ºC) at different intervals of time (5, 10, 15, 20, 25, 30 and 35) minutes. Analysis of Variance of data revealed that time factor showed significant effects on torque (P<0.01). Magnitudes of torque were significantly (P<0.001) different for different fat percentages. Whereas the interaction of time with fat was non-significant (P>0.05). It is proposed that Farinograph may be used for preparation of cheeses because it gives more control on factors affecting cheese preparation.
Keywords: Cheese; Mozzarella; Farinograph-E; Torque